The formation of HuR/YB1 complex is required for the stabilization of target mRNA to promote myogenesis. Issue 3 (11th January 2023) - Sánchez, Brenda Janice; Mubaid, Souad; Busque, Sandrine; de los Santos, Yossef Lopez; Ashour, Kholoud; Sadek, Jason; Lian, Xian Jin; Khattak, Shahryar; Di Marco, Sergio; Gallouzi, Imed-Eddine
Abstract: mRNA stability is the mechanism by which cells protect transcripts allowing their expression to execute various functions that affect cell metabolism and fate. It is well-established that RNA binding proteins (RBPs) such as HuR use their ability to stabilize mRNA targets to modulate vital processes such as muscle fiber formation (myogenesis). However, the machinery and the mechanisms regulating mRNA stabilization are still elusive. Here, we identified Y-Box binding protein 1 (YB1) as an indispensable HuR binding partner for mRNA stabilization and promotion of myogenesis. Both HuR and YB1 bind to 409 common mRNA targets, 147 of which contain a U-rich consensus motif in their 3′ untranslated region (3′UTR) that can also be found in mRNA targets in other cell systems. YB1 and HuR form a heterodimer that associates with the U-rich consensus motif to stabilize key promyogenic mRNAs. The formation of this complex involves a small domain in HuR (227–234) that if mutated prevents HuR from reestablishing myogenesis in siHuR-treated muscle cells. Together our data uncover that YB1 is a key player in HuR-mediated stabilization of pro-myogenic mRNAs and provide the first indication that the mRNA stability mechanism is as complex as other key cellular processes such as mRNA decay and translation.